2013
DOI: 10.1007/s11262-013-0981-4
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of infectious pancreatic necrosis virus isolated from Iranian reared rainbow trout (Oncorhynchus mykiss) in 2012

Abstract: Infectious pancreatic necrosis virus (IPNV) is the causal agent of a highly contagious disease that affects many species of fish and shellfish. This virus causes economically significant diseases of farmed rainbow trout, Oncorhynchus mykiss (Walbaum), in Iran, which is often associated with the transmission of pathogens from European resources. In this study, moribund rainbow trout fry samples were collected during an outbreak of IPNV in three different fish farms in north and west provinces of Iran in 2012; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
4
14
0
3
Order By: Relevance
“…This is particularly evident between the Chilean and the North American isolates (WB and DM) within genotype 4, where the clustering of Chilean isolates could suggest the formation of a fifth genotype. Similar tradeassociated transmissions of IPNV have been suggested for isolates from Spain, Japan, Iran, and Ireland, that show a great similarity with reference strains from the sources where these countries have imported salmonid fish and eggs (Cutrín et al 2004, Nishizawa et al 2005, Ruane et al 2009, 2015, Dadar et al 2013. Concordantly, the phylogenetic trees in these studies also showed grouping among the local isolates and the formation of minor clusters within genogroups.…”
Section: Discussionsupporting
confidence: 77%
“…This is particularly evident between the Chilean and the North American isolates (WB and DM) within genotype 4, where the clustering of Chilean isolates could suggest the formation of a fifth genotype. Similar tradeassociated transmissions of IPNV have been suggested for isolates from Spain, Japan, Iran, and Ireland, that show a great similarity with reference strains from the sources where these countries have imported salmonid fish and eggs (Cutrín et al 2004, Nishizawa et al 2005, Ruane et al 2009, 2015, Dadar et al 2013. Concordantly, the phylogenetic trees in these studies also showed grouping among the local isolates and the formation of minor clusters within genogroups.…”
Section: Discussionsupporting
confidence: 77%
“…IPNV was identified in rainbow trout fry in 2002 (Candan, ), and several reports have described the presence of IPNV in different regions of Turkey (Gurcay, Turan, & Parmaksiz, ; Kalayci, Incioglu, Özyer, & Küçükalİ, ; Ogut & Altuntas, ; Ogut, Altuntas, & Parlak, ). The presence of IPNV in neighbouring Iran was also described recently (Dadar et al., , ; Soltani et al., ). However, the prevalence, genetic and epidemiological relationship between IPNV from farms in different parts of Turkey have not been investigated.…”
Section: Introductionsupporting
confidence: 53%
“…Moving on to Asia, Iranian Sp IPNV isolates obtained from cultured rainbow trout were demonstrated to have the Pro 217 -Thr 221 -Ala 247 profile [101] ( Figure 6K), which disagrees with Song et al [95]. In Mexico [102], IPNV isolates showed Thr at position 221 ( Figure 6L) which is indicative of persistence; however, although most isolates were from asymptomatic carriers-which confirms the predictions-one corresponded to an isolation from diseased rainbow trout.…”
Section: Determinants Of Virulence In Vp2mentioning
confidence: 68%